Elucidation of Genetics of Fibre Yield and Quality Traits in Tossa Jute (Corchorus olitorius L.) Using Generation Mean Analysis - Kale, Vinod Ashok; Roy, Suvendu Kumar; Kundu, Avijit; Vishnupriya, S.; Chakraborty, Moumita; Hijam, Lakshmi; Maying, Bilin; Das, Saikat; Rout, Sanghamitra; Thapa, Bandan; Surje, Dinesh Tulsiram (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted at Uttar Banga Krishi Vishwavidhyalaiya, Cooch Behar, West Bengal, India during Pre-kharif season (premonsoon from April–July) of 2011, 2012 and 2013. It was observed that the six generations, P1, P2, F1, F2, BC1 and BC2 of all the three crosses, differed significantly for all the traits studied, except fibre percentage in case of all the crosses and basal diameter in case of cross C3 (OIN 580×JRO 128). Scaling tests as per Mather (1949) revealed the presence of epistatic interactions for almost all the traits except basal diameter in OIN 580×JRO 128. Duplicate epistasis was observed for majority of the traits and there was total absence of complementary epistasis. The joint scaling test confirmed the inadequacy of the additive-dominance model in most of the crosses for majority of the traits, indicating the influence of duplicate epistasis in their expression. It also revealed a significant additive ×additive (i) and dominance×dominance (l) types of epistasis in all three crosses for fibre yield plant-1, fibre tenacity and fibre fineness. It was thus recommended to opt for pedigree method of conventional breeding with delayed selection to later generations for simultaneous improvement of tossa jute (Corchorus olitorius L.) fibre yield and quality.